Kompetencje pedagogiczne studentów edukacji wczesnoszkolnej jednym z warunków zmiany rozwojowej uczniów - Joanna Nowak (Problemy Wczesnej Edukacji)
Teachers’ work is subjected to constant evaluation by students, parents, other teachers, and society. High demands in the face of changing socio-cultural, educational reality require from teachers the continuous improvement of pedagogical competences. The article raises the question of teachers’ competences acquired by the students of early school education during three years of studies. The scope and type of those competences determine pupils’ developmental change. On the basis of surveys and interviews conducted on 50 students it is possible to formulate numerous conclusions. The most important one indicates that students are comprehensively prepared and gain pedagogical knowledge that allows them to treat pupils subjectively, encourage them to take part in discussions, and organize activities with appropriate methods and forms. Other areas of responsibility may be developed and improved in the course of work.